Total recall [videorecording (Blu-Ray)] - Goldsmith, Jerry; Schwarzenegger, Arnold; Stone, Sharon, 1958-; Ironside, Michael, 1950-; Ticotin, Rachel; Cox, Ronny; Shusett, Ronald; O'Bannon, Dan; Goldman, Gary; Feitshans, Buzz; Povill, Jon; Verhoeven, Paul; et al. (Lionsgate, 2015)
Douglas Quaid is haunted by a recurring dream about a journey to Mars. He hopes to find out more about this dream and buys a holiday at Rekall Inc. where they sell implanted memories. Then something goes wrong with the memory implantation and he remembers being a secret agent fighting against the evil Mars administrator Cohaagen.